Perencanaan Bisnis Cokorasa Bakery di Tarakan - Wahyu Ratnasari; Yudhistira Yudisthira (Departement of Mathematics Education, 2022)
The business plan wantto introduce people to the culinary word with a variety of traditional and modern foods and beverages packed with quality flavors that can be accepted by all walks of life at affordable prices. In running this business using several analyzes includings PEST analysis, %F analysis, Value Chain analysis, 3C analysis, SWOT analysis, and 4P analysis. This analysis is an important aspect in building a business. Break Event point in the Cokorasa Bakery business to get big profit with a large amount of capital. Cokorasa Bakery is located in Tarakan and has a strategic location because Tarakan is a student city in North Kalimantan and business opportunities can be more advanced with lifestyle changes that are increasingly developing in increasingly modern times, and this business plan can open job opportunities for the community and can be a tourist attraction creative economy. As a tool for promoting this business by using social media and colaboration between government and educational institutions as well as SMEs to introduce various kinds of culinary products.